Occurrence of Torsade de Pointes prior to complete lead connection during pacemaker implantation - Yusuke Morita; Junji Morita; Yusuke Kondo; Kazuaki Tanabe (Indian Pacing and Electrophysiology Journal, 2022)
Torsade de Pointes (TdP) can be triggered by a pacing spike on the T-wave, due to pacemaker undersensing. However, it is not widely known that this phenomenon can occur even during pacemaker implantation. An 84-year-old woman underwent pacemaker implantation for the treatment of a complete atrioventricular block with dyspnea. During the procedure, immediately following ventricular lead insertion and before torque wrench tightening, TdP was observed. Ventricular pacing was initiated by inserting the lead into the header of the generator; however, sensing remained unstable. T-waves associated with undersensed PVCs and ventricular pacing occurred simultaneously, resulting in a spike on the T-wave and TdP.